Water leakage due to the welding defect and improvement to reach 1-MW beam operation in the mercury target of J-PARC. Issue 5 (3rd May 2020) - Kogawa, Hiroyuki; Wakui, Takashi; Naoe, Takashi; Haga, Katsuhiro; Takada, Hiroshi; Futakawa, Masatoshi
ABSTRACT: Neutron flux per pulse reached world record at neutron source in Japan Proton Accelerator Research Complex (J-PARC). In the J-PARC, mercury target system is used as a spallation neutron source. A target vessel has a multi-walled protection system that comprises a mercury vessel enclosed with a double-walled water shroud. This is to prevent the leakage of the mercury outside the target vessel. The multi-walled structure needed to be complicated with a lot of welding lines. However, during the operation, we faced an unscheduled shutdown due to water leakage to the intermediate layer between the mercury vessel and water shroud. An investigation on the cause of the leakage was carried out. It is deduced that the leakage path was formed due to the crack propagation from welding defects that are caused by the complicated multi-walled structure. The crack propagation is attributed to the repeated stress by pressure waves generated in the mercury target. Based on the investigation results, the design was improved to remove the welding line on the complicated structure and to realize the stable operation with 1 MW proton beam, which is the final design value of the neutron source in J-PARC.